Development of Instant Puree from Native Potatoes (Solanum andigenum) and Black Mashua (Tropaeolum tuberosum) Fortified with Black Quinoa (Chenopodium quinoa) - Pablo Castañeda; Nancy Chasquibol (Biology and Life Sciences Forum)
In Peru’s Andean region, a diversity of seeds and tubers with high nutritional value and health benefits are grown. Nevertheless, chronic malnutrition and obesity emphasize the need to take advantage of our agricultural wealth to improve public health and ensure sustainable development. The aim of this study was to develop an instant puree with native potatoes (Solanum andigenum) and black mashua (Tropaeolum tuberosum) fortified with black quinoa (Chenopodium quinoa). This study employed a simplex centroid mixture design. The proximal compositions of the three formulations developed were as follows: moisture content of 9.37 ± 0.13% to 9.45 ± 0.06%, ash content of 3.34 ± 0.02% to 3.79 ± 0.17%, protein content of 9.48 ± 0.25% to 11.16 ± 0.38% and total carbohydrate content of 72.81 ± 0.35% to 74.98 ± 0.22%. The samples showed significantly higher antioxidant (7280 ± 113.5 µg trolox/g powder to 12914 ± 604 µg trolox/g powder) and phenolic (3444 ± 241 µg gallic acid equivalent (GAE) /g powder to 7044 ± 322 µg GAE/g powder) content than the control sample. Also, the results of the techno-functional properties of the samples were as follows: water absorption capacity 3.56 ± 0.92 g H2O/g to 3.95 ± 0.07 g H2O/g, solubility 14.45 ± 0.07% to 17.88 ± 0.15% and in vitro protein digestibility 70.27 ± 0.05% to 71.61 ± 0.8%. The samples demonstrated an adequate balance of amino acids compared with the control sample. The sensory characteristics of rehydrated powders were determined. Therefore, in a fast-paced world where convenience food options are part of a continuously expanding market, a nutritionally improved instant puree from ancestral crops is not only more nutritious and tastier but also contributes to sustainability and promotes culinary diversity.